2016
DOI: 10.1080/13510347.2016.1184247
|View full text |Cite
|
Sign up to set email alerts
|

Formal versus traditional institutions: evidence from Ghana

Abstract: Citizens in Ghana have a host of options when it comes to local governance provision as a result of the government's decentralization policies. We undertake to explore and understand how Ghanaians navigate the constellation of local institutions, both formal and traditional, to solve an array of common problems. A four-constituency survey was administered during the summer of 2009 and asked respondents about their experiences interacting with four formal institutions and one traditional institution. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Hypothesis 2 (Public benefits) uses access to electricity as the dependent variable. Although previous research reveals a great many things these communities desire by way of general development (Fridy and Myers, 2019; Myers and Fridy, 2017), electricity is very close to the top of this list. Electricity also proves to be a very good measure of an area’s general level of economic development (Elvidge et al, 2007).…”
Section: Methods: Formulating a Hypothesis Test In An Opportune Casementioning
confidence: 95%
“…Hypothesis 2 (Public benefits) uses access to electricity as the dependent variable. Although previous research reveals a great many things these communities desire by way of general development (Fridy and Myers, 2019; Myers and Fridy, 2017), electricity is very close to the top of this list. Electricity also proves to be a very good measure of an area’s general level of economic development (Elvidge et al, 2007).…”
Section: Methods: Formulating a Hypothesis Test In An Opportune Casementioning
confidence: 95%
“…However, scholars' conclusions on the influence of formal institution on farmers' participation in public affairs have diverged. On the one hand, some scholars have found that formal institutions are by and large working effectively in local governance in Ghana [64]. Formal institutions represent a technology that facilitates control over people and promotes farmers to submit to the government's public administration [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Formal governance arrangements have been established by legal and structural definitions captured in the constitution and other working documents dependent on the context. Traditional governance arrangements, although 'loosely' framed are embedded in local and community culture expressed in the form of rules, norms and beliefs (see also Myers & Fridy, 2016). In Northern Ghana, the activities of rice farmers are informed by both governance arrangements (Nanedo et al, 2014).…”
Section: Socio-institutional Contextmentioning
confidence: 99%